PENINGKATAN MINAT BERBISNIS DAN BERKULIAH PADA REMAJA MELALUI COACHING DI PUSAT PENGEMBANGAN ANAK EPHATA WLINGI BLITAR - Wilma Laura Sahetapy; Widjojo Suprapto; Dhyah Harjanti; Nony Kezia Marchyta; Tesalonika Bani; April Ayu; Yonathan Palumian (Jurnal Padamu Negeri, 2026)
Pusat Pengembangan Anak (PPA) Ephata Wlingi is a church-based child development center that partners with Compassion International in supporting youth development. One of the main challenges faced by the center is the low motivation of adolescents to continue their education to the higher education level. Most of them prefer to work immediately after graduating from senior high school. Responding to this condition, the community service team from the Business Management Program of Petra Christian University implemented a coaching program using interactive presentations and participatory discussions to encourage students to pursue higher education and to develop interest in entrepreneurship with social impact. The coaching activities were designed to broaden participants’ understanding of the importance of higher education, business opportunities, and the role of entrepreneurship in creating value for society. The results showed an increase in students’ awareness of the benefits of continuing to university, the development of new perspectives on business as a career option, and improvement in communication skills and teamwork. The program also encouraged a shift in participants’ mindset from an immediate-work orientation toward longer-term career planning, starting from education, competence development, and experience building. This coaching program indicates that an educational and participatory approach can be an effective strategy to foster motivation for higher education and entrepreneurship among adolescents at PPA, as a foundation for building economic independence and socially impactful ventures.